2010
DOI: 10.1029/2010gl046002
|View full text |Cite
|
Sign up to set email alerts
|

High‐velocity frictional properties of clay‐rich fault gouge in a megasplay fault zone, Nankai subduction zone

Abstract: [1] We conducted high-velocity friction experiments on clay-rich fault gouge taken from the megasplay fault zone in the Nankai subduction zone under dry and wet conditions. In the dry tests, dehydration of clay minerals occurred by frictional heating, and slip weakening is related to thermal pressurization associated with water vaporization, resulting in a random distribution of clay-clast aggregates in the gouge matrix. In the wet tests, slip weakening is caused by pore-fluid pressurization via shear-enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 21 publications
9
97
2
Order By: Relevance
“…The results can be explained by considering that saturation allows the reduction of normal effective stress to very small values, in turn reducing heat production despite the high shearing rate. This is consistent with the results of Ujiie & Tsutsumi (2010) mentioned above.…”
Section: Strain-rate-dependent Friction and Precursory Sliding Motionssupporting
confidence: 83%
See 1 more Smart Citation
“…The results can be explained by considering that saturation allows the reduction of normal effective stress to very small values, in turn reducing heat production despite the high shearing rate. This is consistent with the results of Ujiie & Tsutsumi (2010) mentioned above.…”
Section: Strain-rate-dependent Friction and Precursory Sliding Motionssupporting
confidence: 83%
“…As a rough guide, montmorillonite loses water molecules from interlayers at temperatures , 200°C; kaolinite loses water and transforms into a complex amorphous structure of aluminum and silica compounds at about 550°C and calcite transforms into calcium oxide (CaO) and releases carbon dioxide (CO 2 ) gas at temperatures of 600-850°C. Ujiie & Tsutsumi (2010) report the results of tests performed on clayey gouges in a rotary shear apparatus capable of measuring the shear-band temperature. In saturated samples, temperature increase and reduction of apparent friction under high shearing velocity (in excess of 0·1 mm/s) develop in tandem.…”
Section: Strain-rate-dependent Friction and Precursory Sliding Motionsmentioning
confidence: 99%
“…Investigation of the variability of damage zone thickness is essential to understand the fault mechanism of megasplay faults and is an important goal of this study. Damage zones in the hanging wall are also observed in the modern splay fault at shallow depths in the Nankai Trough but with much thicker width (e.g., Ujiie and Tsutsumi 2010;Rowe et al 2013) possibly due to upward fault migration toward the free surface (e.g., Ramsay and Huber 1987) and/or deformation such as ramp-flat thrusting and folding in the thrust sheet in the uppermost part of the crust (e.g., Ramsay 1992;Suppe 1983), whereas the footwall damage zone is more extensive in the Nobeoka Thrust, suggesting different conditions affecting faults in shallow and deep settings . As fault rocks are buried deeper and as displacement accumulates along the fault, the footwall would have a higher porosity and lower effective strength relative to the hanging wall and may consequently develop thick damage zones in the former .…”
Section: Geologic Setting Of the Nobeoka Thrustmentioning
confidence: 97%
“…However, during the 2011 M w 9.0 Tohoku-Oki earthquake, Japan, coseismic rupture on the megathrust reached the seafloor, producing a huge slip displacement (approximately 80 m) (Ito et al 2011;Ide et al 2011). In addition, recent high-velocity (1.3 m/s) friction experiments on fault zone material in subduction zones showed that an earthquake rupture from deeper portions propagates easily through the updip boundary by high-velocity weakening associated with fluid pressurization and frictional heat (Ujiie and Tsutsumi 2010;Ujiie et al 2013). On the other hand, onland seismic network observations have recorded different types of seismic events called very low frequency (VLF) earthquakes within accretionary prisms (Obara and Ito 2005;Ito and Obara 2006), and recent observations using ocean bottom seismographs have shown a high correlation between VLF events and reverse faulting in a shallow accretionary prism (Obana and Kodaira 2009).…”
Section: Introductionmentioning
confidence: 99%